Kemampuan Membaca Diftong pada Siswa Kelas III Sekolah Dasar Negeri 010 Desa Pengalihan Kecamatan Keritang Kabupaten Indragiri Hilir - Kurniaman, Otang; Antosa, Zariul; Pirawati, Pirawati (Lembaga Yasin AlSys, 2024)
The aim of this research is to determine the ability to read diphthongs in class III students at state elementary school 010, diversion village, Keritang subdistrict, Indragiri downstream district, academic year 2022/2023. This research is qualitative research using a case study approach. The research subjects were third grade students. Data collection used observation and in-depth interview methods. The researcher is the main instrument in the research with the help of observation guidelines and interview guidelines. The data analysis techniques used are data presentation, data reduction, and drawing conclusions. The triangulation used to test the validity of the data is source, time and technique triangulation. The results of the research showed that there were three class III students who were not able to read diphthongs well and correctly, in fact they could not read at all, these students were DI aged 9 years, RR aged 9 years, AS aged 9 years and three students in class III were research subject. This research shows that there are three cases of students who have not been able to read diphthongs properly and correctly.